Preliminary modeling of tsunami potential in the Tanimbar Islands - Eva Susan Ratuluhain; Yunita Angnetjie Noya; Degen E. Kalay; Ronald Darlly Hukubun (Nekton, 2025)
The Tanimbar Islands are an area of high tectonic activity and are part of the outer arc island chain formed by subduction in the Banda zone. The presence of the Sorong Fault and Tanimbar Fault around the Tanimbar Islands also affects the level of vulnerability to earthquakes and tsunami hazards. The purpose of this study was to predict the tsunami potential and affected area of the Tanimbar Islands. The method of analyzing the height data and predicting the affected area used COMCOT v1.7 software. Model simulations were performed on the domain layer by using linear equations. Earthquake and fault parameter data were obtained from the USGS website using historical earthquakes dated January 10, 2023. Bathymetry data were obtained from the GEBO website at a resolution of 15-arcsecond (464 m). The model simulation results show that the initial wave height value marked by the red contour is 0.22 m and the lowest low tide value marked by the blue contour is -0.4 m. Based on these results, the tsunami potential in the Tanimbar Islands is not dangerous, as the potentially affected areas in the study area are Selu Island, Woluaru Island, Wotap Island, and Molu Island, as well as the small islands in the western part. The simulation results demonstrate the importance of research related to tsunami hazards that may occur in the future so that appropriate mitigation can be planned for the existence of small islands around the Tanimbar Islands.